2019
DOI: 10.1038/s41398-019-0633-0
|View full text |Cite
|
Sign up to set email alerts
|

High-dose eicosapentaenoic acid (EPA) improves attention and vigilance in children and adolescents with attention deficit hyperactivity disorder (ADHD) and low endogenous EPA levels

Abstract: No studies have examined the relationship between endogenous polyunsaturated fatty acids (PUFAs) levels and treatment response to PUFAs. We conducted a 12-week, double-blind, placebo-controlled trial comparing the effects of high-dose eicosapentaenoic acid (EPA, 1.2 g) and placebo on cognitive function (continuous performance test) in n = 92 youth (age 6–18-years-old) with Attention Deficit Hyperactivity Disorder (ADHD). Blood erythrocytes PUFAs were measured before and after treatment, to examine the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 47 publications
(63 reference statements)
2
48
0
3
Order By: Relevance
“…A recent study using an animal model of ADHD demonstrated the efficacy of core ADHD symptoms by regulating dopaminergic signaling in the brain 47 . More recently, the reduction of fatty acids in the blood 48 among children and adolescents with ADHD, and similarly, the efficacy of a high dose of eicosapentaenoic acid (EPA) for ADHD symptoms have been reported 49 . Future clinical trials using both existing and novel compounds for ADHD and narcolepsy are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using an animal model of ADHD demonstrated the efficacy of core ADHD symptoms by regulating dopaminergic signaling in the brain 47 . More recently, the reduction of fatty acids in the blood 48 among children and adolescents with ADHD, and similarly, the efficacy of a high dose of eicosapentaenoic acid (EPA) for ADHD symptoms have been reported 49 . Future clinical trials using both existing and novel compounds for ADHD and narcolepsy are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigations have demonstrated that cognitive functions, such as working memory, teacher-rated behavior, and impulsivity, have improved after n-3-PUFA administration in children with ADHD [105][106][107][108][109] . In particular, EPA supplementation seems to elicit small but significant improvement in inattention and hyperactivity symptoms in ADHD patients 103,110,111 . An in vitro study has recently shown that PC12 dopaminergic cells had their viability significantly increased after n-3-PUFA administration 112 , starting with lower doses (from 100 pM).…”
Section: Omega-3 Fatty Acids Adhd and Wnt/mtor-signalingmentioning
confidence: 97%
“…In total, 20 studies focused on supplementation with PUFAs [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] (see Table 1a): fourteen were on patients without comorbidities [34,[36][37][38][40][41][42][43][44][45][46][47]50,53], two with oppositional defiant disorder (ODD) [35,39], and four with various co-diagnoses, such as specific learning disorder, ODD, conduct disorder, tic disorder, anxiety, Tourette syndrome, or psychomotor difficulties [48,49,51,52]. Two researches [42,43] include very small samples.…”
Section: Methodologiesmentioning
confidence: 99%
“…These studies supplemented with various omega-3 fatty acids. In total, 18 studies provided docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) [34][35][36][37][38][39][40][41][42][44][45][46][47][48][49][50]52,53], one study provided alpha linolenic acid (ALA) [43], and one study did not specify which omega-3 was used. Three studies supplemented omega-6: one used gamma-linolenic acid (GLA) [36], while two did not specify which omega-6 was used [35,51].…”
Section: Cprs-rmentioning
confidence: 99%